Impact and management of left ventricular function on the prognosis of Takotsubo syndrome - El-Battrawy, Ibrahim; Ansari, Uzair; Lang, Siegfried; Behnes, Michael; Schramm, Katja; Fastner, Christian; Zhou, Xiao-Bo; Kuschyk, Jürgen; Tueluemen, Erol; Röger, Susanne; Borggrefe, Martin; Akın, Ibrahim (European journal of clinical investigation, 2017)
Background Early research has proposed that patients with Takotsubo syndrome (TTS) could have a higher mortality rate than the general population. Our study was conducted to determine the short- and long-term outcome of TTS patients associated with a significantly compromised left ventricular function on hospital admission. Materials and methods Our institutional database constituted a collective of 112 patients diagnosed with TTS between 2003 and 2015. The patients were classified into two groups based on the left ventricular ejection fraction (LVEF), with those presenting with a LVEF > 35% on admission categorized into one group (n = 65, 58%) and those presenting with LVEF ≤ 35% (n=47, 42%) categorized into another group. The endpoint was the all-cause of mortality over a mean follow-up of 1529 ± 1121 days. Results Preliminary results indicated that patients with an EF ≤ 35% had a significantly greater risk of developing life-threatening arrhythmias, and were much more likely to suffer from cardiogenic shock. Patients often required varying forms of mechanical respiratory support. The in-hospital mortality, 30-day mortality, 1-year mortality and ongoing long-term mortality was significantly higher in TTS patients with an EF ≤ 35%. In a multivariate Cox regression analysis, an EF ≤ 35% (HR 3·3, 95% CI: 1·2-9·2, P < 0·05) was identified as a strong independent predictor of the primary endpoint. Conclusions In-hospital events as well as short- and long-term mortality rates among TTS patients diagnosed with a significantly reduced LVEF on admission were significantly higher. There is an urgent need for randomized trials, which could help define uniform clinical management strategies for high risk TTS patients.